Efficient neural coding in auditory and speech perception - Gervain, Judit (Trends Neurosci, 2018)
Speech has long been recognized as “special”. Here, we suggest that one of the reasons for speech being special is that our auditory system has evolved to encode it in an efficient, optimal way. The theory of efficient neural coding argues that our perceptual systems have evolved to encode environmental stimuli in the most efficient way. Mathematically, this can be achieved if the optimally efficient codes match the statistics of the signals they represent. Experimental evidence suggests that the auditory code is optimal in this mathematical sense: statistical properties of speech closely match response properties of the cochlea, the auditory nerve, and the auditory cortex. Even more interestingly, these results may be linked to phenomena in auditory and speech perception.